2003
DOI: 10.1080/08880010390203071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Chosen Parameters of the Immune System in Children with Acute Lymphoblastic Leukemia

Abstract: The immunosuppressive effect of cytostatics, basic therapeutic agents in the treatment of proliferative diseases of the hematopoietic system, and the rising number of children cured from acute leukaemias form together a need to monitor the status of the immune system following cessation of therapy. Surface antigens in lymphocytes from peripheral blood were assessed in 16 children directly after intensive chemotherapy (i.e., after protocol II of the BMF program) and in 25 children 12-13 months following conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…In the present study, when we analysed receptor expression by group in order to evaluate the activity-receptor relationship, the CD16 + CD56 + (NK cell) population was significantly reduced in the group that had completed protocol M and the group receiving maintenance chemotherapy compared to controls. Similar to our study, Mazur et al compared the CD16 + CD56 + population in children with ALL immediately after completing protocol II and 1 year later to a control group and found this cell population to be lower in the group receiving intensive chemo- therapy compared to the other groups (28). In a prospective study by Eyrich et al, 20 standard and intermediate-risk pediatric patients with ALL who had not received radiotherapy were evaluated in terms of cellular and humoral immunity at various stages of chemotherapy.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, when we analysed receptor expression by group in order to evaluate the activity-receptor relationship, the CD16 + CD56 + (NK cell) population was significantly reduced in the group that had completed protocol M and the group receiving maintenance chemotherapy compared to controls. Similar to our study, Mazur et al compared the CD16 + CD56 + population in children with ALL immediately after completing protocol II and 1 year later to a control group and found this cell population to be lower in the group receiving intensive chemo- therapy compared to the other groups (28). In a prospective study by Eyrich et al, 20 standard and intermediate-risk pediatric patients with ALL who had not received radiotherapy were evaluated in terms of cellular and humoral immunity at various stages of chemotherapy.…”
Section: Discussionsupporting
confidence: 88%
“…This phenomenon was previously documented by other authors. 21 – 23 In contrast, Jarosz et al 24 revealed that children at this stage of therapy are characterized by significantly decreased percentage and absolute count of NKs.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies dealing with the problem in question involved patients who completed the complex therapy of ALL; however, the period between the withdrawal of the therapy and NK count determination varied between 1 day and more than 5 years. 23 , 25 , 26 Our study focused on the analysis of the effects of many-week ALL remission maintenance therapy on NKs; therefore, we analyzed the percentage and absolute count of these cells 2 weeks after completing the treatment. Following this period, the direct reducing effect of cytostatics on peripheral blood leukocytes, including lymphocytes, resolves.…”
Section: Discussionmentioning
confidence: 99%
“…Sitostatiklerin yan etkilerinden biri de immün sistemi baskılamasıdır. İmmün sistem disfonksiyonları hem kalitatif hem de kantitatifdir (6) . Kombine kemoterapinin öncüleri bu immün disfonksiyonun farkında olmuşlar ve tedavi altındaki çocuklarda immün fonksiyonları güçlendirmek için aralıklı BCG uygulamaları gibi çeşitli girişimlerde bulunmuşlardır (7) .…”
Section: Discussionunclassified